Morphological, physical, thermal, and mechanical properties of carbon nanotubes reinforced arrowroot starch composites - Habib, Abdul; Mohd Sapuan, Salit; Zainudin, Edi Syams; Atiqah, Afdzaluddin (Walter de Gruyter GmbH, 2025)
It is necessary to uniformly disperse carbon-based nanoparticles within a biopolymer matrix. However, in most cases, carbon nanotubes (CNTs) tend to form agglomerates within the biopolymer matrix due to their hydrophobicity, lack of compatibility, and weak interfacial interaction with the matrix. This study involved the fabrication of nanocomposite films utilizing a simple solution casting approach. The films were made from plasticized starch derived from arrowroot starch (ARS) and multi-walled CNTs. Different amounts of CNTs (0–1 wt%) were used in the films. The CNTs were subjected to ultrasonic treatment to reach a uniform dispersion within the arrowroot starch. The ARS/CNTs nanocomposite films were characterized by physical properties, Fourier Transform Infrared Spectroscopy, X-ray diffraction, Thermogravimetric analysis, and mechanical properties. The presence of CNTs effectively restricts the paths available for water molecules, resulting in an enhanced water barrier. The tensile strength of 1% CNTs-reinforced film was 9.14 MPa (increased by 174%). This suggests improved dispersion of CNTs in the ARS matrix as a result of the establishment of strong hydrogen bonds with the ARS matrix. Furthermore, this also demonstrates the effectiveness of ARS as a biopolymer, since it has the ability to form strong bonds with the CNTs filler without causing agglomeration inside the matrix.